Synthesis of sulfides via reaction of aryl/alkyl halides with S8 as a sulfur-transfer reagent catalyzed by Fe3O4-magnetic-nanoparticles-supported L-Histidine-Ni(II). (4th May 2017) - Azadi, Gouhar; Taherinia, Zahra; Naghipour, Ali; Ghorbani-Choghamarani, Arash
ABSTRACT: One-pot synthesis of symmetrical diaryl/alkyl sulfides in high yields from the reaction between aryl/alkyl halides and S8 can be carried out in a short period, using Fe3 O4 @SiO2 @His@Ni(II) as a reusable catalyst. The present approach offers the advantages of a clean reaction, simple methodology and high efficiency, and avoids the use of a toxic catalyst. GRAPHICAL ABSTRACT: